Efecto de la tintura de matico (buddleja globosa) para el tratamiento de gingivitis en caninos domésticos (canis lupus familiaris)” - Peralvo Vaca, María de los Ángeles (2021)
The present research aimed to evaluate the efficacy of the application of Matico tincture (Buddleja globosa) for the control of a bacteria presents in the oral cavity in domestic canines diagnosed with gingivitis, through general clinical and bacteriological examination, the experimentation was carried out in Salcedo City and the sample was taken from 30 adult male and female canine patients which came to the consultation in a period of one month, the experimental work handled three treatments: T1 application of 70% ethyl alcohol, T2 application of tincture of Matico every day every 12 hours and T3 application of Matico tincture passing one day every 12 hours, each treatment consisted of 10 canines and the gums were cleaned by using a sterile gauze each tooth with its corresponding gingiva, and the days application depended according to the specification of each treatment, to assess the efficacy of the dye, two samples were taken from each animal, at 15 days and 30 days after starting the treatments, in which the number and percentage of colony forming units (CFU) were assessed, the results showed that the colonizing bacteria in the oral cavity of the canines examined: Proteus spp, Staphylococcus spp , Escherichia coli and Streptoccus spp showed percentage sensitivity in CFUs, but more effectively showed a response towards Proteus spp, being T2 the one with the best antimicrobial effect, showing a 63.93% decrease on day 15 and 33.77% on day 30 of CFUs to bacteriological examination, starting from 100% colonization on day 1 before starting treatment.